Association of the rs1990760, rs3747517, and rs10930046 polymorphisms in the IFIH1 gene with susceptibility to autoimmune diseases: a meta-analysis - Xiao, Zilin; Luo, Shuoming; Zhou, Yuemin; Pang, Haipeng; Yin, Wenfeng; Qin, Jiabi; Xie, Zhiguo; Zhou, Zhiguang (Frontiers in Immunology, 2023)
Objective: The aim of this study was 1) to examine the association of a single-nucleotide polymorphism (SNP) rs1990760 of the interferon induced with helicase C domain 1 (IFIH1) gene with type 1 diabetes (T1D) in a Chinese population, and 2) to explore whether the IFIH1 SNP rs1990760, rs3747517, and rs10930046 play a role in modifying the genetic risk of autoimmune diseases. Methods: A total of 1273 T1D patients and 1010 healthy control subjects in a Chinese population were enrolled in this case-control study. Subsequently, we perform a meta-analysis about the association of the rs1990760, rs3747517, and rs10930046 polymorphisms in the IFIH1 gene with susceptibility to autoimmune diseases. The studies that evaluated the association between IFIH1 rs1990760, rs3747517, and rs10930046 and autoimmune diseases were retrieved. The random and fixed genetic effects model were used to evaluate the association and the effect sizes including Odds ratios (OR) and 95% confidence intervals (CI). We performed stratification analyses based on ethnicity and type of autoimmune diseases. Results: Rs1990760 was not associated with a significant risk of T1D in the Chinese population in the case-control study. A total of 35 studies involving 7,0966 patients and 12,4509 controls were identified and involved in this meta-analysis. The meta-analysis results displayed significant associations between IFIH1 rs1990760 and rs3747517 polymorphisms and autoimmune diseases risk (OR=1.09, 95%CI: 1.01~1.17; OR=1.24, 95%CI: 1.15~1.25, respectively). Stratified analysis indicated a significant association between rs1990760 and rs3747517 and the Caucasian populations (OR=1.11, 95%CI: 1.02~1.20, OR=1.29, 95%CI: 1.18~1.41, respectively). Conclusions: This study revealed no association between IFIH1 SNP rs1990760 and T1D in Chinese. And further meta-analysis indicated that rs1990760 and rs3747517 polymorphisms, but not rs10930046, confer susceptibility to autoimmune diseases, especially in Caucasian populations.